Efektivitas Strategi Kooperatif Jigsaw pada Pembelajaran Komputer Jepang - Rosita Ningrum (Humaniora, 2014)
This study began with the researcher’s interest to transform learning strategy in Japanese computer which has been longstanding in conventional way. In previous studies the Jigsaw cooperative strategy had been tested in the exact sciences in College. The researcher was challenged to bring the instructional materials of Japanese computer which are felt quite hard by students to be easier with mutual assistance. Heavy load materials are minimized. Learners must actively explore materials; it is not only from the teacher. The Jigsaw cooperative strategy was tested on three-semester students in order to determine the effectiveness of Jigsaw cooperative in Japanese computer learning. This study used pure experiment. The design involved two groups of subjects, one given by the experimental treatment with the Jigsaw cooperative strategy (experimental group) and the other group (control group) with usual learning technique. Data were taken in two ways: quantitative by making instruments such pretest and posttest to the two classes and qualitative by interview to complete the descriptive data analysis result. Furthermore, all results of the pretest and posttest were analyzed by measuring the normality and t-test to determine how the Jigsaw strategy successfully applied on the samples. To collaborate the results, the interviews were transcribed to see the response from samples on the Jigsaw cooperative strategy in Japanese computer learning. Results of the test data analysis in the experimental group and the control group showed that the Jigsaw cooperative strategy was proved more effective in Japanese computer learning than the conventional method usually used.